"How to" operate a pediatric neuropsychology practice during the COVID-19 pandemic: Real tips from one practice's experience. Issue 2 (17th February 2021) - Loman, Michelle; Vogt, Elisabeth; Miller, Lauren; Landsman, Rachel; Duong, Priscilla; Kasten, Jessica; DeFrancisco, Danielle; Koop, Jennifer; Heffelfinger, Amy
ABSTRACT: This paper aims to provide pediatric neuropsychologists with suggested processes and procedures to continue to provide neuropsychology services during the COVID-19 global pandemic. Our practice is located within an academic medical center/children's hospital, and setting-specific recommendations may not extend to all practices, though our hope is that others find guidance from our approach to providing pediatric neuropsychology evaluations when physical distancing is required. With consideration of ethics, equity, and assessment validity, we provide suggestions for a) modifying practices around seeing patients during COVID-19, b) tele-health for the pediatric neuropsychologist, c) safety standards and requirements, and d) working with special populations (e.g., Autism Spectrum Disorder, bilingual populations, immunocompromised patients, and acute inpatient assessment).